A LINC00472-encoded polypeptide impedes migration and proliferation through modulation of the HDAC2/SP1 axis in non-small cell lung cancer cells - Lei Xu; Haoyong Kuang; Haodong Peng; Sen Wu; Yu Bai; Xiangbo Jia; Wenjian Yao (Cancer Cell International)
Abstract Objective While long non-coding RNAs (lncRNAs) are increasingly recognized as sources of functional micropeptides, their roles in non-small cell lung cancer (NSCLC) remain poorly characterized. This study investigates the therapeutic potential and molecular mechanism of LINC00472-encoded polypeptide in NSCLC. Methods Through integration of ribosome profiling, transcriptomics, and co-expression analysis, we systematically identified lncRNA-encoded polypeptides in NSCLC. Translational competence was validated via ribosome affinity purification (TRAP), Western blot, and immunofluorescence (IF). Functional assays (CCK-8, EdU, wound healing, transwell) and xenograft models assessed anti-tumor effects. HDAC2/SP1 interaction dynamics were analyzed by co-IP and luciferase reporter systems. Results Multi-omics screening identified LINC00472 as a bifunctional transcript encoding a 15-aa polypeptide (LINC00472-ORF). LINC00472-ORF exhibited potent tumor-suppressive activity, reducing NSCLC proliferation and motility in vitro, while suppressing xenograft growth in vivo. Mechanistically, LINC00472-ORF disrupted HDAC2/SP1 interaction, inducing SP1 hyperacetylation, cytoplasmic retention, and transcriptional inactivation of downstream oncogenic genes. Conclusion We unveil LINC00472-ORF as a dual-function therapeutic agent that targets the HDAC2/SP1 axis to inhibit NSCLC progression. Graphical Abstract